Talleres de danza infantil para desarrollar la motricidad gruesa en los niños y niñas del primer año de E.G.B de la escuela nueve de octubre, cantón Pujilí, provincia de Cotopaxi período 2012-2013 - Chacha Gavilema, Diana Nataly (2013)
The research is based on the necessity for dance workshops. There are children difficulties in developing gross motor skills. You need to find the best solution. This will be applied at "Nueve de Octubre" School, in Pujilí, Canton, and Cotopaxi Province, 2012-2013. Trained Teacher acquires new skills and methodologies thus acquiring skills in dance workshops that will facilitate the teaching-learning process in motor development. This will allow the implementation programs. Also, it helps to toddlers can cope and achieve troubleshoot difficult moments in their daily life. It concerns gross motor skills.